Possible involvement of long non-coding RNAs GNAS-AS1 and MIR205HG in the modulation of 5-fluorouracil chemosensitivity in colon cancer cells through increased extracellular release of exosomes - Azwar, Shamin; Ng, Chin Tat; Zahari Sham, Siti Yazmin; Seow, Heng Fong; Chai, Minhian; Ghazali, Mohd Faizal; Jabar, Mohd Faisal (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
A growing number of studies have suggested the involvement of long non-coding RNAs as the key players in not just the initiation and progression of the tumor microenvironment, but also in chemotherapy tolerance. In the present study, generated 5-FU-resistant SW480/DR cells were analyzed via cDNA microarray for its aberrant lncRNAs and mRNAs expression in comparison with the 5-FU-susceptible SW480/DS cells. Among the 126 lncRNAs described, lncRNAs GNAS-AS1, MIR205HG, and LOC102723721 have been identified to be significantly upregulated, while lncRNs lnc-RP11-597K23.2.1-2, LOC100507639, and CCDC144NL-AS1 have been found to be significantly downregulated. In the meantime, bioinformatic analysis through gene ontology studies of aberrantly expressed mRNAs revealed “regulated exocytosis”, among others, as the biological process most impacted in SW480/DR cells. To investigate, exosome purification was then carried out and its characterization were validated via transmission electron microscopy and nanoparticle tracking analysis. Interestingly, it was determined that the 5-FU-resistant SW480/DR cells secretes significantly higher concentration of extracellular vesicles, particularly, exosomes when compared to the 5-FU-susceptible SW480/DS cells. Based on the lncRNA-mRNA interaction network analysis generated, lncRNA GNAS-AS1 and MIR205HG have been identified to be potentially involved in the incidence of 5-FU resistance in SW480 colon cancer cells through promoting increased release of exosomes into the intercellular matrix. Our study hopes not only to provide insights on the list of involved candidate lncRNAs, but also to elucidate the role exosomes play in the initiation and development of 5-FU chemotherapy resistance in colon cancer cells.